Theater-Based Role-Playing Learning Model for Enhancing Students' Verbal Communication Skills in Indonesian Language - Antari, Luh Desy; Putu Aditya Antara; Ni Ketut Desia Tristiantari (Jurnal Ilmiah Sekolah Dasar, 2025)
The low level of students' verbal communication skills affects their ability to interact socially in the community and to understand learning materials that require active engagement with the teacher. As a result, students often express frustration when encountering materials or questions containing difficult vocabulary. This study aims to analyze the effect of the Theater-Based Role Playing learning model on the verbal communication skills in Indonesian language of second-grade elementary school students. This research employed a quasi-experimental design, specifically the Non-Equivalent Pre-test Post-test Only Control Group Design. The population consisted of all second-grade students from 8 elementary schools, totaling 102 students. The sampling technique used was cluster sampling, with classes randomly assigned as intact groups, comprising 26 students in the experimental group and 24 students in the control group. Data on students' verbal communication skills in Indonesian were collected using a non-test method through a teacher observation performance checklist consisting of 24 items. The data were analyzed using a t-test, yielding tcount = 11.49 and ttable = 2.01. Since tcount (11.49) > ttable (2.01), H1 is accepted and H0 is rejected. Therefore, it can be concluded that the Theater-Based Role Playing learning model has a significant effect on the verbal communication skills of second-grade students.